2002
DOI: 10.1016/s0167-9317(01)00582-2
|View full text |Cite
|
Sign up to set email alerts
|

Tantalum carbide and nitride diffusion barriers for Cu metallisation

Abstract: The reactions in the Si/TaC/Cu and Si/Ta 2 N/Cu metallisation systems were investigated by x-ray diffraction, Rutherford backscattering, scanning electron microscope and the transmission electron microscopy. The results were then combined with the assessed ternary SiTa-C, Ta-C-Cu, Si-Ta-N and Ta-N-Cu phase diagrams. It was found that both barriers ultimately failed due to diffusion of Cu through the barrier and accompanied formation of Cu 3 Si at temperatures higher than 725 °C. However, in the TaC barriers th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…It has been observed that when Cu/Mo 2 C/Si structure is annealed at temperature 700 8C, a number of bright particles of varying sizes from 1 to 2 mm appeared. With the further annealing of structure at 800 8C, the size of these white particles reaches to 5-10 mm as compared to 20-30 mm in case of sputter deposited Cu/TaC/Si system [14]. These bright regions were characterized as MoSi 2 and Cu 3 Si using EDX elemental mapping technique.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been observed that when Cu/Mo 2 C/Si structure is annealed at temperature 700 8C, a number of bright particles of varying sizes from 1 to 2 mm appeared. With the further annealing of structure at 800 8C, the size of these white particles reaches to 5-10 mm as compared to 20-30 mm in case of sputter deposited Cu/TaC/Si system [14]. These bright regions were characterized as MoSi 2 and Cu 3 Si using EDX elemental mapping technique.…”
Section: Resultsmentioning
confidence: 97%
“…In order to keep the advantages of scaling technology, the past decade has seen the tremendous efforts in terms of the developing new process technology, materials and their combinations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Since the performance of the future IC technology will be limited by the resistance of the metal interconnects [8], copper metallization is emerging as the alternative to aluminum due to its low electrical resistivity (1.72 mV cm), high melting temperature (1084 8C), high electro-migration resistance and also high stress voiding resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained microstructure, which is not always reported in the literature, is greatly dependent on the process parameters. Moreover impurities, especially oxygen, may have a strong effect on kinetics also, as previously reported for Ta and TaC diffusion barriers by Laurila et al [3,17] and Clevenger et al [18]. No data have been reported for the thermal stability of TaN/Ta/ TaN barriers.…”
Section: Thermal Stability Of Tan and Tan/ta/tan Barrier Layersmentioning
confidence: 86%
“…Recently, an application other than as a resistor material is as the diffusion barrier layer of copper wiring in the routing technology of integrated circuits [3]. Many reports have discussed the deposition of the TaN x thin film, but most of these studies focused on the resistance of the thin film itself and reports related to the contact resistance with the electrode have not appeared.…”
Section: Introductionmentioning
confidence: 99%